1998
DOI: 10.1046/j.1469-1809.1998.6250379.x
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to spina bifida; an association study of five candidate genes

Abstract: Clues regarding candidate genes which influence susceptibility to spina bifida and anencephaly come from the identification of folate-associated risk factors and from studies of mouse mutants showing neural tube anomalies. On this basis we selected five candidate genes ; CBS, MS, MTHFR, T (Brachyury) and BRCA1 for genetic analysis in 31 Dutch and 48 British NTD families. Ten polymorphisms, two for each gene, were used in transmission tests for disequilibrium (TDT). In six instances more than 50 transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 43 publications
4
75
3
Order By: Relevance
“…51 Other gene-environment 52 and genegene interactions 52,53 might also occur. If feasible, interactions between maternal and fetal genotype should also be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…51 Other gene-environment 52 and genegene interactions 52,53 might also occur. If feasible, interactions between maternal and fetal genotype should also be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Folate metabolism and homocysteine levels are connected with several clinical disorders, including coronary artery disease, deep venous thrombosis, neural tube defects, and cancer (see Gailey and Gregory 15 for review); the thermolabile variant has been associated in different studies with increased risk of each of these diseases. 13,14,16 -20 However, despite the biologic plausibility of these associations, none have been reproducibly observed across many studies (for example, Ma et al [21][22][23] ).…”
Section: Review Of the Association Study Literaturementioning
confidence: 99%
“…The 68-bp insertion in the exon 8 of the gene appeared to be associated with an increased risk in several studies. [46,[52][53]. Multiplicative interaction of the CBS 68-bp insertion with the homozygosity for the MTHFR 677CT variant was showed to confer a five-fold increased risk for NTDs children, The MTHFR mutation alone had a two-fold increased risk, whereas there was no risk for CBS mutant genotype alone.…”
Section: Variantmentioning
confidence: 99%
“…[45] The methionine synthase (MTR), a vitamin B 12 -dependent enzyme, utilizes 5-methyltetrahydrofolate, generated by MTHFR, for homocysteine remethylation to methionine. A polymorphism of the MTR gene, the 2756AG (D919G) that lead to the substitution of an aspartic acid with a glycine residue, has been studied in several studies, but the majority have not reported a significant association [36,40,[46][47][48].…”
Section: Variantmentioning
confidence: 99%